2020
DOI: 10.3389/fphys.2020.00666
|View full text |Cite
|
Sign up to set email alerts
|

Does Acupuncture Benefit Delayed-Onset Muscle Soreness After Strenuous Exercise? A Systematic Review and Meta-Analysis

Abstract: Purpose: This systematic review and meta-analysis was designed to evaluate the effects of acupuncture intervention on alleviating delayed onset of muscle soreness (DOMS) after intense exercise. Method: Randomized controlled trials (RCTs) were searched from online databases including Medline (PubMed), Cochrane Library, Web of Science, Embase, PsycINFO, China Knowledge Resource Integrated Database (CNKI), and Wanfang (Chinese) up to April 2019. Data points were extracted from the eligible RCTs at the time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(54 reference statements)
1
3
0
5
Order By: Relevance
“…The difference between the acupuncture intervention and control groups is quite large; therefore, one can infer that acupuncture will produce clinically important reductions in DOMS in healthy adults. Our findings agree with earlier studies [41][42][43][44][45][46] that found classical acupuncture and tender points were more effective than sham or no acupuncture in reducing VAS values for pain up to 72 hours following the induction of DOMS.…”
Section: Discussionsupporting
confidence: 93%
“…The difference between the acupuncture intervention and control groups is quite large; therefore, one can infer that acupuncture will produce clinically important reductions in DOMS in healthy adults. Our findings agree with earlier studies [41][42][43][44][45][46] that found classical acupuncture and tender points were more effective than sham or no acupuncture in reducing VAS values for pain up to 72 hours following the induction of DOMS.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are methods with lack of scientific evidence of their effectiveness or contradictory data. The first group includes kinesiotaping, contrast baths, and acupuncture [ 13 , 14 , 15 , 16 , 17 , 18 ]. The second group of methods most likely includes cyclic compression therapy, stretching, general cryotherapy, and sauna use [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Muskelkater tritt meist nach ungewohnt ausgeprägter Belastung auf [1,2] und ist verstärkt bei vorrangig exzentrischer Kontraktion [2]. Es gibt keinen einzelnen Grund für das Auftreten von Muskelkater, vielmehr ist er Folge eines Ablaufs von physiologischen Prozessen, welche die verschiedenen Qualitäten des Muskelkaters über einen Verlauf von 24-72 Stunden bedingen [2].…”
Section: Kommentarunclassified